Adoption Of RFID Toll Payment Among Consumers On Highways In Penang Malaysia - shamsuddin, alina; Lim, Zhen Liang (Research in Management of Technology and Business, 2023)
: Malaysia’s toll system has been one of the causes of traffic congestion on major highways. One of the reasons for this is that users need to stop or slow down to pay the toll. As technology has advanced over the years, especially radio frequency identification (RFID), we can expect faster response times from the devices. Despite RFID seems to be self-contained to avoid massive congestion, the technology still has problems. One of the barriers, is the reading errors. Moreover, the use of RFID technology by retailers and government agencies raises questions on possible breaches of personal information privacy and potential security threats to personal information. Consumer acceptance of RFID technology is a complex issue, but a major concern for consumers may be the utility of the technology. In this study, the researchers aim is to identify the level of adoption of RFID technology by consumers and the influencing factors of RFID adoption on highways in Penang, Malaysia. Quantitative method was adopted for this study. Statistical Package for Social Sciences (SPSS) was used to analyse data. According to the results of the analysis, perceived usefulness has emerged as the most significant factor, with a mean of 4.106. Furthermore, the level of intention towards RFID use on highways is strong. This study has a significant impact on several parties, including as a reference for government and authorities to better understand RFID users’ satisfaction with RFID technology on highways and how the influencing factors of RFID toll payment will affect RFID adoption intentions.